Effects of Workplace Parent Management Training on Marital and Job Satisfaction among Iranian Working Parents - Mousavi, Masoumeh; Alavinezhad, Ramin; Moosavi, Arezoo (Frontiers in Sociology, 2017)
Background Shifting the focus of parent management training (PMT) to parents and discussing implications for maximizing the outcomes of PMT for the entire family is new and promising. Objective We aimed to examine the efficacy of work place PMT on job and marital satisfaction among staff members of an academic center. Methods We held 8 PMT sessions (1.5 h each) for 20 staff members who were parents to children in the age range of 2–12 years. Dyadic Adjustment Scale (DAS) and Occupational Descriptive Index [Health and Safety Executive (HSE)] were used for baseline and post-intervention data gathering. DAS higher scores indicate higher marital adjustment satisfaction and higher HSE scores indicate higher occupational stress. To analyze changes in HSE and DAS scores over time, paired t-test and Wilcoxon signed rank test were used, respectively. Results All DAS subscales show significant increased from baseline to the final session except for affectional expression which was not significant. We found no significant changes in total or subscale HSE scores among participants. Conclusion Findings of this study underscore the role of psycho-education usage in work environment and provide evidence about the importance of designing interventions concerning working parents. Implications of PMT are discussed in the text.